2018
DOI: 10.2478/prilozi-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Treatment in Children Born Small for Gestational Age (SGA)

Abstract: Introduction: Growth failure is a common consequence in small for gestational age (SGA) children. Patients and Methods: The growth patterns and serum insulin like growth factor 1 (IGF1) concentrations before and after the 1st year under growth hormone treatment of 32 short stature SGA born children have been evaluated. In addition, we investigated the insulin like growth factor 1 receptor (IGF1R) exon 2 as a hotspot for IGF1R genetic alterations. It is of note that no dysmorphic features were observed in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Being born small for gestational age (SGA) is a major determinant of childhood and later life morbidity, including metabolic syndrome, neurodevelopmental deficits and coronary heart disease (Arcangeli et al 2012; Jancevska et al 2012). Established risk factors known to impact fetal growth include maternal age, parity and ethnicity (Jancevska et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being born small for gestational age (SGA) is a major determinant of childhood and later life morbidity, including metabolic syndrome, neurodevelopmental deficits and coronary heart disease (Arcangeli et al 2012; Jancevska et al 2012). Established risk factors known to impact fetal growth include maternal age, parity and ethnicity (Jancevska et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Being born small for gestational age (SGA) is a major determinant of childhood and later life morbidity, including metabolic syndrome, neurodevelopmental deficits and coronary heart disease (Arcangeli et al 2012; Jancevska et al 2012). Established risk factors known to impact fetal growth include maternal age, parity and ethnicity (Jancevska et al 2012). In addition to maternal characteristics, gestational exposure to environmental pollutants through maternal ingestion and inhalation are also known to play a role (Chou et al 2011; Lauritzen et al 2016; Peelen et al 2016; Stillerman et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, LBW has been reported to be associated with increased risks for diseases including cardiovascular disease, type 2 diabetes, end-stage renal disease, and schizophrenia (Negrato and Gomes, 2013;Alexander et al, 2014;Zhang et al, 2014). Jancevska et al (2012) reported that SGA people had an increased incidence of metabolic syndrome, coronary artery disease, stroke, low bone density, and osteoporosis. A high BW has been regarded as associated with increased risks of type 2 diabetes and obesity (Johnsson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Babies with LBW or babies born as small-forgestational-age are disadvantaged early in life. They have higher risks of hypoglycemia, hyperbilirubinemia, respiratory distress syndrome, low APGAR score with the resultant poor quality of life with approximately 20 times increased risk of neonatal death more than babies born as appropriate-for-gestational-age weight [8,9,10,11]. Negrato and Gomes have demonstrated a clear relationship between LBW and increased risk of many diseases later in life, such as insulin resistance, cardiovascular diseases, renal diseases [12], etc.…”
Section: Introductionmentioning
confidence: 99%